Password-authenticated searchable encryption - Chen, Liqun; Huang, Kaibin; Manulis, Mark; Sekar, Venkkatesh (International journal of information security, 2021)
We introduce Password Authenticated Searchable Encryption (PASE) , a novel searchable encryption scheme where a single human-memorizable password can be used to outsource (encrypted) data with associated keywords to a group of servers and later retrieve this data through the encrypted keyword search procedure. PASE ensures that only the legitimate user who knows the initially registered password can perform these operations. In particular, PASE guarantees that no single server can mount an offline attack on the user’s password or learn any information about the encrypted keywords. The concept behind PASE protocols extends previous concepts behind searchable encryption by removing the requirement on the client to store high-entropy keys, thus making the protocol device-agnostic on the user side. In this paper, we model the functionality of PASE along with two security requirements (indistinguishability against chosen keyword attacks and authentication) and propose an efficient direct construction in a two-server setting those security we prove in the standard model under the Decisional Diffie–Hellman assumption. Our constructions support outsourcing and retrieval procedures based on multiple keywords and allow users to change their passwords without any need for the re-encryption of the outsourced data. Our theoretical efficiency comparisons and experimental performance and scalability measurements show that the proposed scheme is practical and offers high performance in relation to computations and communications on the user side. The practicality of our PASE scheme is further demonstrated through its implementation within a JavaScript-based web application that can readily be executed on any (mobile) browser and remains practical for commodity user devices such as laptops and smartphones.